The Spirit in Mark: Power and Suffering - Charette, Blaine (Pneuma, 2021)
Abstract There are fewer direct references to the Holy Spirit in Mark’s Gospel than in the other gospels. For this reason, there has been much less discussion of the significance of the Spirit to Mark’s theology in comparison with other gospels, particularly Luke and John. Yet in the case of Mark it is not helpful or appropriate to assess the importance of this subject based merely on the frequency of use of certain key terms. Of greater importance is the placement of references to the Spirit within the narrative structure of the Gospel and the manner in which the Spirit is brought into relation to other themes and topics that are central to the interests of the Gospel.